2008
DOI: 10.1073/pnas.0800658105
|View full text |Cite
|
Sign up to set email alerts
|

Huntington's disease protein contributes to RNA-mediated gene silencing through association with Argonaute and P bodies

Abstract: Huntington's disease is a dominant autosomal neurodegenerative disorder caused by an expansion of polyglutamines in the huntingtin (Htt) protein, whose cellular function remains controversial. To gain insight into Htt function, we purified epitope-tagged Htt and identified Argonaute as associated proteins. Colocalization studies demonstrated Htt and Ago2 to be present in P bodies, and depletion of Htt showed compromised RNA-mediated gene silencing. Mouse striatal cells expressing mutant Htt showed fewer P bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
114
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(128 citation statements)
references
References 43 publications
14
114
0
Order By: Relevance
“…These data support a role for HTT in ciliogenesis/ ciliophagy (52). A loss of WT HTT function may similarly cause dysregulation of RNA-mediated gene silencing because HTT associates with Argonaute and P bodies/stress granules, both shown to be cleared by selective autophagy/granulophagy (53)(54)(55). These associations suggest that many of the phenotypic consequences caused by loss of HTT function can be understood in terms of disrupted selective autophagy.…”
Section: Discussionmentioning
confidence: 54%
“…These data support a role for HTT in ciliogenesis/ ciliophagy (52). A loss of WT HTT function may similarly cause dysregulation of RNA-mediated gene silencing because HTT associates with Argonaute and P bodies/stress granules, both shown to be cleared by selective autophagy/granulophagy (53)(54)(55). These associations suggest that many of the phenotypic consequences caused by loss of HTT function can be understood in terms of disrupted selective autophagy.…”
Section: Discussionmentioning
confidence: 54%
“…Mutant Htt Purifications Implicate Altered RNA MetabolismWe have previously demonstrated that wild-type Htt functions with argonaute 2 (Ago2, the catalytic component of the RNAinduced silencing complex) in a post-transcriptional gene silencing pathway (14) and is also involved in RNA transport in cultured cortical neurons (48,49). The current study points to Htt function in protein synthesis through its interactions with ribosomal proteins, various translation initiation factors, and other accessory proteins.…”
Section: ϫ10mentioning
confidence: 56%
“…Protein identification and quantification analysis were done with Integrated Proteomics Pipeline (IP2, Integrated Proteomics Applications, Inc. San Diego, CA) using ProLuCID, DTASelect2, and Census. Tandem mass spectra were extracted into ms1 and ms2 files (14) from raw files using RawExtract 1.9.9. Poor quality spectra were removed from the dataset using an automated spectral quality assessment algorithm (17).…”
Section: Fractionation Of Brain Tissue and Affinity Purifications-mentioning
confidence: 99%
“…20,21 Rhes, a striatal-specific guanine nucleotide-binding protein, interacts preferentially with polyQ-expanded Htt and induces its sumoylation, leading to cytotoxicity. 22 Interactors of Htt include several proteins related to RNA processing; 23,24 however, their relation to the polyQ expansion has not been elucidated. Two systematic studies of the Htt interactome have been reported to date: Wanker and coworkers used yeast two-hybrid screens to describe a protein interactions network for HD.…”
Section: Resultsmentioning
confidence: 99%
“…Mutant Htt associates with Ago2 in P bodies and contributes to RNA-mediated gene silencing. 23,24 P bodies, unlike SG, are not associated with ribosome and mostly serve for storage and degradation of repressed mRNAs. P bodies contain decapping enzymes and endonucleases and may associate with components of RISC complex (argonaute, DICER).…”
Section: Discussionmentioning
confidence: 99%